Pen: Solution for Food Freshness - Willy Dwirayudha; Anita Maharani (Publikasi Indonesia, 2026)
This research aims to design and develop a sustainable ice block business model as a solution to the problem of imbalance between the demand and supply of ice blocks in coastal areas, especially in supporting the sustainability of the capture fisheries sector. Ice blocks have a strategic role in maintaining the freshness of fish catches, but in various coastal areas of Indonesia, there are still limitations in production capacity, difficult distribution access, and inflexible purchasing patterns, which have an impact on declining the quality of fishery products and fishermen's income. This study used a qualitative approach with the Business Model Creation method. Data was collected through literature studies, document analysis, field observations, and interviews with business actors and fishing communities. The analysis framework used includes the Empathy Map, Value Proposition Canvas, Business Model Canvas, PESTEL analysis, and Porter's Five Forces to understand market needs, industry dynamics, and the feasibility of the business model developed. The results show that the PEN: Solution for Food Freshness business model offers key values in the form of stable ice availability, production and distribution efficiency, and support for food quality and safety. This model is expected to increase the competitiveness of ice businesses, have a positive impact on the local economy and fisheries sustainability. Further research is needed to compile financial projections, renewable energy applications, and social and environmental impact measurements.